ANALISIS KOMPETENSI SUMBER DAYA MANUSIA DALAM HUBUNGANNYA DENGAN PRESTASI KERJA DISPERINDAG PROVINSI. SULAWESI SELATAN - Erwin Horas (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2020)
The purpose of this study was to determine the effect of human resource competence on employee work performance of DISPERINGAG PROV. SULSEL. This research is a quantitative research. The entire population is the sample in this study. The research data were obtained from the results of respondents' responses using a questionnaire using a Likert scale. The data analysis method used in this research is validity test, reliability test, and linear regression analysis test using the SPSS program. The results of this study indicate that the competence of human resources has a positive and significant effect on the work performance of DISPERINDAG PROV employees. SULSEL. This is evidenced by the results of the t test, the independent variable affects the dependent variable by 3.676 with a significance level of 0.000.